Minoritas Muslim di Barat (Studi atas Pemikiran Tariq Ramadan) - Moh. Zeinudin (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
Post September 11 2011 tragedy, being a Muslim in Western countries is a challenge. Tariq Ramadan with his books stands appearing as one of press secretaries trying to break down the negative stereotype of Islam in Western Countries. Ramadan shows the empirical data of Muslims plurality and progressivity whether it relates to quantity or quality manner that colorizes its civilization. Tariq Ramadan states that such progressivity illustrated clearly the fact that the center of Islam is not only in Middle East Countries but also is potential in Western Countries.